Winner and loser positions - Changing development process of Hungary and Slovakia in the past decade - Nagy, Zoltan; Gyorffy, Ildiko (НТУ "ХПИ", 2009)
After the change in the political system, any necessary changes did not occur regarding many fields of the Hungarian economic and social life: after the millennium it started to lag behind the countries in East Central Europe, and in the increasingly growing competition it is forced to loose significant position. Defective decisions in field of economic policy resulted that the country became file-closer among altering economies. With the most significant macro economical indicators that are signed in the study, the loser Hungarian position is traceable.After the change in the political system, any necessary changes did not occur regarding many fields of the Hungarian economic and social life: after the millennium it started to lag behind the countries in East Central Europe, and in the increasingly growing competition it is forced to loose significant position. Defective decisions in field of economic policy resulted that the country became file-closer among altering economies. With the most significant macro economical indicators that are signed in the study, the loser Hungarian position is traceable.

После изменения в политической системе необходимые изменения не произошли в экономической и общественной жизни Венгрии: на заре нового тысячелетия Венгрия отстала от стран Центрально-Восточной Европы, и постепенно теряет свои позиции в соперничестве с ними. Ошибочные решения в области экономической политики закончились тем, что Венгрия стала последней среди стран с переходной экономикой этого региона. С помощью макроэкономических индикаторов это доказывается